Radio frequency probes for ultra-high field magnetic resonance imaging - Lee, Daniel James (2011)
This thesis describes the design, construction and testing of a dome coil. The dome coil is hemispherical in shape and is intended to be used within a set of hemispherical gradient coils in a seven tesla magnetic resonance imaging magnet. The dome coil has eight independent elements and is designed to be used for parallel transmission and reception. It is shown that the dome coil produces less specific absorption rate than a conventional birdcage coil and is suitable for head imaging. A study of travelling wave magnetic resonance imaging is also presented. In this study two different methods of generating a travelling wave (using a patch antenna and an end-fire helix antenna) are compared, and the power requirements and specific absorption rate of the travelling wave approach are considered. It is concluded that travelling wave magnetic resonance imaging is best performed using a local receive coil and with the travelling wave antenna placed at least 50 cm from the subject. All theory relevant to the design, construction, testing and use of these coils and antennas is also presented.